Optimised tools for toxicity assessment of biochar-amended soils - Amaro, António Manuel de Andrade Lapa (2014)
The growing interest in large-scale biochar application to soils, either for improving crop yield, as a tool for carbon sequestration or for replacing inorganic fertilizers, highlights the urgency for an effective evaluation of potential negative effects on soil biota, and the soil processes and functions that they mediate. While the field of biochar ecotoxicology is becoming more important, studies that focus on biochar effects on selected terrestrial species remain scattered and lacking environmental, ecological and practical relevance. This study focused on adapting and optimising a range of ecotoxicological and ecological tools (that have been established or standardized for contaminated soils), in order to test their suitability for evaluating the toxic potential of biochar-amended soils. Firstly, it was tested the suitability of invertebrate avoidance behaviour assays (using earthworms, collembolans and isopods) to assess the potential toxicity of soils enriched with wood-biochar, alone and in combination with traditional compost, over a 5 month period, in a real field trial at the Estação Vitivinícola da Bairrada. Nevertheless, there is increasing need for more representative conditions in testing, that account for longer study durations and greater environmental (e.g. soil moisture, temperature) and ecological variation (e.g. interactions among co-existing test organisms and their vertical distribution in soil). The second part of this work therefore, focused on optimizing a methodology using Small-scale Terrestrial Ecosystem Models (STEMs) containing earthworms and plants, for higher-tier studying of the potential ecological impact of manure-biochar on terrestrial ecosystems, at reported application rates. Results suggest that avoidance behaviour responses using representative invertebrates can be used for evaluating the impact of wood-biochar on soil biota, in a real case application, over 5 months. This can have implications for complementing other strategies for characterizing or managing biochar field applications, such as help with the choice of biochar type and safe application rates. Further, the use of STEMs containing earthworms and turnip seeds exposed to manure biochar under more representative conditions, has shown to be more conservative when compared to the standardised single species test and therefore, may be adequate as higher-tier evaluation of the toxic potential of soils with manure biochar. Studies like the present can be an important contribution for establishing suitable biochar risk assessment methodologies and support both, on-going development of biochar standardization schemes and development of adequate biochar regulations.